Impact of freeze-thaw cycles on organic carbon and metals in waters of permafrost peatlands - Payandi-Rolland, Dahédrey; Shirokova, Liudmila S.; Labonne, Fabian; Bénézeth, Pascale; Pokrovsky, Oleg S. (Chemosphere, 2021)
Despite the importance of soil and surface waters freezing in permafrost landscapes, the behaviour of dissolved organic carbon (DOC), nutrients and metals during periodic freeze-thaw cycles (FTC) remains poorly known. The on-going climate warming is likely to increase the frequency of FTC in continental aquatic settings, which could modify the chemical composition of waters. In this study, we conducted 9 repetitive cycles of overnight freezing (−20 °C) and 5 h thawing (4 °C) in the laboratory using representative 0.22 μm-filtered waters from NE European permafrost peatland: leachates of vegetation and soil, and natural surface waters (depression, thermokarst lake and river). Only minor (<5%–15%) changes of DOC concentrations, SUVA254 and molecular weight were observed in all leachates and the depression water. In contrast, several trace elements (Fe, Al, P, Mn, As, and REE) exhibited sizable variations during FTC (>10%). The leachates and the depression water were enriched in trace elements, whereas the thermokarst lake and the river demonstrated a decrease in concentration of Fe (−39 and −94%, respectively), Al (−9 and −85%), and Mn (−10 and −79%) during FTC. Overall, the observations demonstrated an increase in aliphatic low molecular weight organic matter (OM), and the precipitation of Fe, Al hydroxides and organo-mineral particles. Therefore, enhanced of frequency of FTC can favour the release of metals and toxicants from acidic OM-rich surface waters and maintain stable OM-metals-colloids in large lakes and rivers, thus regulating aquatic transport of DOC and metals from soils to the Arctic Ocean.